Small atrophic testis in infant: Should it be excised? or preserved? - Mitsumasa Okamoto; Harunori Miyauchi; Hiroaki Fukuzawa (Elsevier, 2022)
Background: We have struggled to decide whether the unilateral atrophic testis without external genital abnormalities, which we call a "small atrophic testis (SAT)", should be preserved or removed, because no definitive reviews of surgical outcomes have yet been reported. Purpose: The aim of this study was to clarify the outcomes of our surgical management and to outline our surgical strategy for SATs. Methods: 5 cases in SAT were evaluated. Outcomes of surgery including bilateral testicular size were analyzed retrospectively. Results: Retrospective studies of SAT cases with surgical intervention showed that the amount of affected testicular tissue has an impact on the pathogenesis of compensatory contralateral testicular hypertrophy (CCTH), but other factors may also be associated with the development of CCTH. Conclusion: We assume that one should remove an SAT that is very small at surgery or displays progression of atrophy on follow-up ultrasonography even after fixation because there may be a risk of seminomas developing from atrophic testes.